2008
DOI: 10.1097/pas.0b013e318164c3f0
|View full text |Cite
|
Sign up to set email alerts
|

Careful Exclusion of Non-neoplastic Brain Components is Required for an Appropriate Evaluation of O6-methylguanine-DNA Methyltransferase Status in Glioma

Abstract: Evaluation of O6-methylguanine-DNA methyltransferase (MGMT) expression is important for antiglioma therapy as many clinical trials have demonstrated that promoter hypermethylation and low level expression of MGMT are associated with an enhanced response to alkylating agents. However, here we report that the current strategies used to evaluate MGMT status in gliomas are unreliable. We observed discordance in the MGMT expression status when immunohistochemical evaluation and polymerase chain reaction-based methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…As tumour samples were chosen to have 470% neoplastic cells, these data suggest variation in the numbers of methylated tumour cells in different regions of glioblastoma tissues. Similarly, glioblastomas show heterogeneous patterns of MGMT protein expression often with regions within the same tumour displaying widely different staining patterns (Juillerat-Jeanneret et al, 2008;Sasai et al, 2008). On the basis of the MSP assay and bisulphite sequencing some studies have claimed homogeneity in MGMT status within glioblastomas (Grasbon-Frodl et al, 2007), whereas others have reported a degree of intratumoral heterogeneity (Juillerat-Jeanneret et al, 2008;Parkinson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As tumour samples were chosen to have 470% neoplastic cells, these data suggest variation in the numbers of methylated tumour cells in different regions of glioblastoma tissues. Similarly, glioblastomas show heterogeneous patterns of MGMT protein expression often with regions within the same tumour displaying widely different staining patterns (Juillerat-Jeanneret et al, 2008;Sasai et al, 2008). On the basis of the MSP assay and bisulphite sequencing some studies have claimed homogeneity in MGMT status within glioblastomas (Grasbon-Frodl et al, 2007), whereas others have reported a degree of intratumoral heterogeneity (Juillerat-Jeanneret et al, 2008;Parkinson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the extent of methylation within the tumour impacts on associations with survival. This may be a reflection of the proportions of cells with silenced MGMT, but the relationship between methylation and expression of active enzyme has been questioned (Maxwell et al, 2006;Sasai et al, 2008). Alternatively, high numbers of methylated cells may be a marker of less aggressive biology, possibly in association with methylation of other gene promoters .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite pseudosubstrates of MGMT such as O 6 -benzylguanine were expected to suppress resistance by depleting MGMT (8)(9)(10), clinical trials did not show significant restoration of temozolomide sensitivity in patients with temozolomide-resistant GBM (11). Therefore, other therapeutic agents which suppress MGMT expression and sensitize the efficacy of temozolomide are highly desired (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Many glioblastomas contain a considerable proportion of non-neoplastic cells such as macrophages/microglia (tumor-associated macrophages) that can comprise over 70% of the tumor. [21][22][23][24][25] Interference of tumor-associated macrophages is illustrated by the improvement in interpretation of MGMT (O-6-methylguanine-DNA methyltransferase) status of glioblastoma using immunohistochemistry. 26 That tumor-associated macrophages obscure the telomere maintenance mechanism is suggested by molecular similarities between glioblastomas classified as having the non-defined telomere maintenance mechanism and those typed as alternative lengthening of telomeres or telomerase positive.…”
mentioning
confidence: 99%